Managing price risk for physical oil products with derivatives on the Bulgarian local market - Anton Angelov (2012)
This diploma thesis will focus on the management tactics used to cope with the price risk of physical oil products with the use of derivatives. As price risk can be defined as an unfavourable movement of a price of a product in a future point, many factors must be taken into consideration. But as the oil market is covered by an incomprehensive fog, that maybe only a few people in the world posses the power to unveil, the precise quantification of all factors could never be accomplished to a degree of one hundred percent. This is why the focus of this thesis will be on the following points: - risk identification, measurement and mitigation - derivatives and their use in praxis - price and currency risk - major price formation factors for crude and oil distillates - local and global benchmarks - specifics of the Bulgarian local market In short this diploma thesis aims to present and analyse the derivative instruments in order to provide an overview of the oil markets and the way market participants can deal with the innate risk exposure. Although there are many information sources like Platt’s, Bloomberg, Reuters, OPEC, IEA, ICE, NYMEX and many business services like PricewaterhouseCoopers (PWC), Citigroup, KPMG, it is important to note that the existing data is not always 100% complete and that recommendations and forecast should be followed at one’s own responsibility.